PENGARUH KEMAMPUAN MERESPON TUTURAN TUTOR DAN PENGUASAAN KOSAKATA TERHADAP KEMAMPUAN BERBICARA WARGA BELAJAR PAKET C DI SKB KENDAL - Melati Indri Hapsari; Bibit Sholekhah (JIV-Jurnal Ilmiah Visi, 2009)
This research aimed at discovering the effects of ability to respond the tutorâ€™s narration and mastery of vocabulary to speaking skill of Package C students in Kendal Learning Activity Cente(LAC). The research population covered the Package C students of the second grade. Sampels were selected randomly and a set of test was used to collect the data to be analysed statistacally. The findings show that the ability to respond the tutorâ€™s narration and vocabulary mastery give significant contribution to the speaking ability of the Package C students in Kendal LAC. Based on the findings, the research recommends narrative approach model as one of the techniques in learning vocabulary.